ENGLISH LANGUAGE LEARNING IN MODERN EDUCATION SYSTEM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This scientific article discusses the importance of the English language in the modern education system, methods of teaching English, innovative technologies in language learning, and the role of English in global communication. The article also analyzes the significance of English in science, business, technology, and international cooperation. Furthermore, problems related to English language teaching and possible solutions are highlighted.
Keywords: English language, education, modern technologies, communication, innovation, language skills, globalization, online learning.